Hubungan Antara Dukungan Keluarga Dengan Tingkat Depresi - Sulisworo Kusdiyati; Hendro Prakoso; Nina Rahayu (SCHEMA (Journal of Psychological Research), 2011)
The aim of this study was to gain empirical information about the correlation between the support of family and the level of depression among breast cancer sufferers who have mastectomy at Bandung Hasan Sadikin Hospital. This study used correlational method. Subject of this study was 20 patients, all of breast cancer suferrers who have mastectomy between one and two years, 30-45 years old, have spouse, still fertiled, had been medicated while this study performed, and enrolled at Oncology Clinic Hasan Sadikin Hospital. The hypothesis was the higher family support the lower level of depression of cancer breast sufferers who have mastectomy at Bandung Hasan Sadikin Hospital. The instrument which used to collecting data about family support was a scale which contructed by the researcher based on Sarafino’s Social Support Theory (1994), and Beck Depression Inventory was used to obtain the level of depression. Both of data was ordinal data, so the Rank Spearman correlation technique was used to analyze the data. The result was rs = -0,494, it means that the higher family support the lower level of depression among breast cancer sufferers who have mastectomy at Bandung Hasan Sadikin Hospital.